Conserving wild dogs ( Lycaon pictus ) outside state protected areas in South Africa: ecological, sociological and economic determinants of success - Du Toit, J.T. (University of Pretoria, 2013)
Thesis (DPhil (Zoology))--University of Pretoria, 2006.